EFFICIENCCY ANALLYSIS OF TAX REVENUES AND AXCESS BUDGET REMAINING ON INDONESIA’S CAPITAL EXPENDITURE - Finta Sapridah; Hijri Juliansyah (Journal of Malikussaleh Public Economics, 2020)
This studys aims to analyze the efficiency of tax revenues and SILPA on capiital expenditures for each Province in Indonesia. This studying uses time-series data, which includes inputt and outputt variabels: Tax revenue, SILPA, and capital Expenditures for 2016-2018 the method of used in this study is the data Envellopment Analysiis program 2.1 to evaluate the performances of an activity in an entity or organizational unit. The Result of this data Envelopment analysis show that in 2018 only 9 Provinces achieved the levell of capitall expenditures efficiency, consisting of the provinces of Aceh, South Sumatra, DKI Jakarta, Maluku, Papua, Nort Maluku, Gorontalo, West Papua, and West Sulawesi.Keywords: Capital expenditures, Taxes, SILPA, data envelopment analysis.